Da educação danificada à formação da autonomia - Furmann, Leandro (2007)
In this dissertation work it aims to rebuilding of the current education and its critical perspective guided by the idea of the rational and moral formation of the subjects starting from the critic to the instrumental rationality of Adorno and Horkheimer. Starting of the Kant formation conception for the majority, the seeks, after analyzing the damage provoked by the Enlightenment project education by the reductionism of the instrumental rationality to point possible elements so that one can think and to implement an education tends for reference the education concept for the resistance of Adorno